UNDERSTANDING STUDENTS’ FINANCIAL BEHAVIOR THROUGH LIFESTYLE AND OPEN INNOVATION PERSPECTIVES - Dinarossi Utami; Frecilia Nanda Melvani; Anggrelia Afrida (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The rapid growth of digital financial innovation has increased the complexity of financial decision-making among university students. Although financial literacy is commonly viewed as a key driver of financial behavior, prior studies report inconsistent results, indicating a persistent knowledge–behavior gap. Addressing this gap, this study examines the roles of financial attitude and lifestyle as mediating mechanisms linking financial literacy to students’ financial behavior, grounded in the Theory of Planned Behavior and an open innovation perspective. The study aims to analyze the direct and indirect effects of financial literacy on financial behavior among university students. Data were collected from 398 students across public and private universities and analyzed using PLS-SEM with SmartPLS 4. Measurement model assessment confirmed adequate reliability and validity, followed by structural model and mediation analyses. The results indicate that financial literacy has significant positive effects on financial attitude, lifestyle, and financial behavior. However, lifestyle emerges as the strongest predictor and the only significant mediator, while financial attitude does not mediate the literacy behavior relationship. These findings demonstrate that financial behavior is shaped more by daily consumption patterns than by attitudinal factors alone. This study contributes by extending TPB within an open innovation and complexity framework, emphasizing lifestyle based mechanisms as a key pathway for transforming financial knowledge into actual behavior.